Isolation of multi-drug resistant Escherichia coli from hospital wastewater and adjacent community water samples in Dhaka city, Bangladesh - Mim, Sanjida Akter; Maisha, Humaira Tabassum; Subha, Silma; Tabassum, Tahia (Brac University, 2024)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Microbiology, 2023.